2021
DOI: 10.1038/s41592-021-01276-3
|View full text |Cite
|
Sign up to set email alerts
|

SEAM is a spatial single nuclear metabolomics method for dissecting tissue microenvironment

Abstract: Spatial metabolomics can reveal intercellular heterogeneity and tissue organization. To achieve highest spatial resolution, we reported a novel Spatial single nuclEar metAboloMics (SEAM) method, a scalable platform combining high resolution imaging mass spectrometry (IMS) and a series of computational algorithms, that can display multiscale/multicolor tissue tomography together with identification and clustering of single nuclei by their in situ metabolic fingerprints. We firstly applied SEAM to a range of wil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 81 publications
2
92
0
Order By: Relevance
“…In this manuscript, we have reviewed the biological and computational basis of spatial transcriptomics analysis, with an example of cell type mapping and downstream applications in kidney tissue. Spatial transcriptomics technologies are evolving at a rapid pace and extending beyond transcriptomics into metabolomics and proteomics ( Lundberg and Borner, 2019 ; Ganesh et al, 2021 ; Yuan et al, 2021 ). The integration of unbiased spatial omics technologies will provide a powerful set of tools to characterize disease processes in intact tissue ( Dries et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…In this manuscript, we have reviewed the biological and computational basis of spatial transcriptomics analysis, with an example of cell type mapping and downstream applications in kidney tissue. Spatial transcriptomics technologies are evolving at a rapid pace and extending beyond transcriptomics into metabolomics and proteomics ( Lundberg and Borner, 2019 ; Ganesh et al, 2021 ; Yuan et al, 2021 ). The integration of unbiased spatial omics technologies will provide a powerful set of tools to characterize disease processes in intact tissue ( Dries et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on SOTIP detected tumorimmune boundary, we also detected proteins with previously unreported spatial polarization. In the novel task of DME analysis, we firstly compared a fibrotic liver sample with healthy liver sample 7 , then identified MECNs specifically enriched in the fibrotic sample. The spatial localization and cellular composition of the detected MECN is consistent with the histology image.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in healthy vertebrate liver, the zonation patterns of hepatocytes perform mutual effect on the microenvironment within liver lobules 4 . While during liver fibrosis, there occurs metabolic alteration around the liver-fibrotic microenvironment 7 . In cancer, researchers also reported that different patterns of immune infiltration were associated with patient survival [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MALDI, SIMS, DESI, LA-ESI), MSI technique has been successfully applied to detect synthetic drugs, metabolites, lipids, peptides, proteins, metals, glycans, etc 7,8,9,10 . A multiplex molecular changes caused by disease progression or drug intervention can be visualized at the whole-body, organ, tissue, cell or even sub-cellular resolution 11,12,13,14 . This unique advantage in spatially resolved multiplex molecular detection makes MSI promising in drug research and development (R&D) 15,16 .…”
Section: Introductionmentioning
confidence: 99%